2012
DOI: 10.1007/s10035-012-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vibration on solid-to-liquid transition in small granular systems under shear

Abstract: The effect of vibration on the solid-to-liquid-like transition of a dense granular assembly under planar shear is studied numerically using soft particle molecular dynamics simulations in two dimensions. We focus on small systems in a thin planar Couette cell, examining the bistable region while increasing shear, with varying amounts of vertical vibration, and determine statistics of the shear required for fluidization. In the absence of vibration, the threshold value of the shear stress depends on the prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…While in our previous work we focused on the mesoscopic scale granular mechanics associated with dynamic triggering of slip events, here we focus on the role of the vibration parameters, specifically on vibration amplitude, and we analyze vibration amplitude dependencies from a statistical point of view. Similar 2D and 3D studies by DEM simulations have been performed by Capozza et al [47] and Melhus and Aranson [48]. Capozza et al investigated the role of the boundary vibration frequency in determining an overall reduction of the macroscopic friction of the granular layer, while Melhus and Aranson studied the role of the vibration amplitude and frequency implementing the vibration as a fictional bulk force applied to each particle of the granular layer.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…While in our previous work we focused on the mesoscopic scale granular mechanics associated with dynamic triggering of slip events, here we focus on the role of the vibration parameters, specifically on vibration amplitude, and we analyze vibration amplitude dependencies from a statistical point of view. Similar 2D and 3D studies by DEM simulations have been performed by Capozza et al [47] and Melhus and Aranson [48]. Capozza et al investigated the role of the boundary vibration frequency in determining an overall reduction of the macroscopic friction of the granular layer, while Melhus and Aranson studied the role of the vibration amplitude and frequency implementing the vibration as a fictional bulk force applied to each particle of the granular layer.…”
Section: Introductionmentioning
confidence: 55%
“…Beyond the laboratory study performed by Johnson et al [11,16], the systematic role of applied ac vibration in anticipating slip events has been documented from a statistical point of view only by Melhus and Aranson, via 2D DEM simulations of a more simplified sheared granular layer, in the absence of deformable bounding blocks [48]. Instead of the time to failure, they monitored the shear strength of the system, i.e., the shear stress value achieved by the system at the moment of the slip onset.…”
Section: A Effectiveness Of Boundary Vibration In Dynamic Triggeringmentioning
confidence: 99%
“…Applying external vibrations is known experimentally to affect rheological properties and hysteresis (8,10,13,32,37,38), as we now quantify. Even small typical noise can generate very rare events where noise is locally large, leading to rearrangements and creep flow.…”
Section: External Noise In Granular Flowsmentioning
confidence: 92%
“…Numerical simulations have shown that this transition can be achieved by imposing mechanical vibrations: the system, initially in the stick-slip regime, undergoes a continuous sliding above a given vibration threshold. The mechanical vibrations both reduce the friction when their amplitude increases 11 , and trigger an order/disorder transition in the dense granular assembly 7 12 13 .…”
mentioning
confidence: 99%
“…These results are in contradiction with the very low acceleration value needed to unjam a granular hopper with vibrations 16 or with the strain wave amplitude threshold, of the order of 10 −7 to 10 −6 for a moderate sized earthquake, often proposed for dynamic earthquake triggering 3 17 18 . The role of frequency, when considered, is still debated, whether in the dry 11 13 19 or wet case 20 21 .…”
mentioning
confidence: 99%